The Problem of Youth’s Sexual Education in the Narrative Sources (20-30’s of the XX Century) - Kravchenko, Tetyana (Pedagogical Discourse, 2013)
The article considers the problem of sexual education in the period of the 20-30’s of the XX century and its reflection in the narrative sources. During the publication, the author reveals the features of the sexual upbringing of the youth of the allocated period, highlights the impact of the state’s political transformations on the domestic approaches to solving the problems of children’s and youth’s sexual education. The author stresses the need for an objective analysis of the historical-pedagogical sources, notes the particular importance of narrative sources, enriching the scientific knowledge of living facts and phenomena. The report analyzes some sources of young people sex education problem in the 20-30’s of the XX century.